Conditions and Causes of Successful Conversion of Brownfields - Švorc, Martin (2014)
The topic of this thesis is an adaptation of non-functioning objects, relics of ironworks owned by Vítkovice Machinery Group. Clarified is theoretical ambiguity regarding the forms of industrial heritage conservation as a major cause of late onset of their conversion. Analysed are some contemporary phenomena accompanying the preparation for the conversion in practice. Its delayed but relatively fast process of conversion is examined. Against the background of emerging European trend the change of functions of old buildings is evaluated to meet the cultural needs of modern society. The goal of the thesis is to give a clear and logical picture of problems and situation. The analysis of both of those elements gives assumptions suitable for formulating of conclusions that may be taken as certain warnings and possible recommendations to potential investors.